2018
DOI: 10.1139/facets-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of natural antioxidants from olive oil with fig and date palm fruit extracts on biochemical and hematological parameters in rats during diethylnitrosamine-induced carcinogenesis

Abstract: Diethylnitrosamine (DEN) is a well-known carcinogen. The aim of our study was to determine the role of olive oil (7 g/kg) with fig (1 g/kg) (OF) and (or) date palm (1 g/kg) (D) fruit extracts during DEN treatment of male Wistar rats. The OF-DEN and (or) D-DEN groups were given oral antioxidants daily for two weeks before and during DEN treatment (21 weeks).The DEN-treated group showed dramatic results for all investigated parameters as compared with the control rats. All OF-DEN and D-DEN groups showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The administration of OFD to DOX-treated and (or) R-treated rats improves the hematological parameters (RBC, Hb, Hct, platelets, total, and differential WBCs), which might be attributed to increased antioxidant enzymes leading to diminished oxidative stress in bone marrow and the spleen. The results of our study are in agreement with the results of studies by Viola and Viola (2009) and Fathy et al (2018) who attributed the improved hematological parameters to oleuropein, a component of olive oil, which also exerts a favorable action on the platelets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The administration of OFD to DOX-treated and (or) R-treated rats improves the hematological parameters (RBC, Hb, Hct, platelets, total, and differential WBCs), which might be attributed to increased antioxidant enzymes leading to diminished oxidative stress in bone marrow and the spleen. The results of our study are in agreement with the results of studies by Viola and Viola (2009) and Fathy et al (2018) who attributed the improved hematological parameters to oleuropein, a component of olive oil, which also exerts a favorable action on the platelets.…”
Section: Discussionsupporting
confidence: 92%
“…NO is a small, diffusible, highly reactive molecule that can generate oxidative stress (Millar 2004;Fathy et al 2018). The significant decrease in NO levels recorded in the liver tissue after DOX and (or) R treatment might be the result of its interaction with superoxide to form peroxynitrite (Pryor and Squadrito 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that there was no mortality or toxic signs up to 5000 mg/kg and the % body weight change in POFE/B/KOH/ABND and the group of mice that were treated with ABND were 9.5% and -0.15%, respectively. The results of our study agree with the results of studies by Viola and Viola (2009) and Fathy et al (2018). The results showed that the activities of ALT and AST were increased in the group of mice that were treated with POFE/B/KOH/ABND, and ABND when compared to the normal control and NOFE control groups.…”
Section: Discussionsupporting
confidence: 91%